Model of social handling fordrugs relapse abusers in North Sumatra, Indonesia - Husni Thamrin, Agus Suriadi (Opción, 2019)
The purpose of this research is to observe how the social handling model is conducted to the drug relapse misusage. A qualitative and descriptive method is used to achieve its objectives, besidesdata collection is done through literature study, in-depth interviews, and observation. The results showed that there is no significant social therapy for the drug relapse abusers at Pamardi Putra Social House "Insyaf" of North Sumatra. Furthermore, the provision of vocational training is the provision of productive skills that can be capital for clients/residents after leaving the rehabilitation center to avoid the suggestion to use drugs again